Brand Community Building in Peer-to-Peer sharing – The case of Blablacar - JACQUE, Laura (2014)
Collaborative consumption is a new form of consumption based on sharing practices that is becoming increasingly popular nowadays. Previous studies on this topic have already investigated various types of collaborative consumption and they reveal that collaborative consumption supports community building, yet some results are contrasting. Additionally, despite the amount of previous research, there is a lack of research focusing on peer-to-peer sharing of individual possessions. This study explores the community formation in a peer-to-peer sharing system, particularly it aims to understand whether brand community can be built in a peer-to-peer sharing system, to identify barriers and/or incentives to community formation and the outcomes of engaging in consumer-to-consumer interactions. Peer-to-peer sharing is examined in the context of ride-sharing via qualitative interviews of Blablacar consumers. The findings confirm that brand community can be built through peer-to-peer sharing, however, the community is quite fragile and characterized by a weak commitment. The findings also identify the benefits of being a part of the community, which are utilitarian as well as social. The theoretical and practical implications of the findings are discussed.